Standardization of Tulsi Taila: An Ayurvedic oil based medicine. - Shah, Shruti; Patil, Sonali (Journal of Drug Delivery and Therapeutics, 2019)
Tulsi (Ocimum sanctum) is cultivated near Hindu houses and temples throughout India. In Ayurvedic medicine, leaves, seeds and root of this plant are being used either alone or in combination with others. The chemical composition of Tulsi is highly complex, containing many nutrients and other biological active compounds.Ayurvedic formulations are safe and effective but adulteration of lower cost material in it reduces the quality of the drug, hence the standardization of herbal drugs is necessary. Present study involves preparation and standardization of Tulsi oil for determination of its standard parameters as per monograph to maintain the safety, uniformity and quality production of the product. Essential oil of Tulsi extracted from holy basil (Ocimum tenuiflorum) which is then used in combination with coconut oil and fenugreek seeds.The major uses are as bug repellent,deodorizer, for releivijng skin problems, dental problems, in fever,chronic cough and cold, bronchitis etc. The parameters tested for the Tulsi oil include Organoleptic evaluation, physicochemical and Phytochemical evaluation,chromatographic analysis for active constituents and stability studies. All the parameters were tested as per pharmacopeia standards.Keywords: standardization, tulsi oil, ayurveda., essential oil.